2000
DOI: 10.1111/j.1530-0277.2000.tb02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective Diagnosis of Alcohol Abuse: Compared Values of Carbohydrate‐Deficient Transferrin (CDT), γ‐Glutamyl Transferase (GGT), and Mean Corpuscular Volume (MCV)

Abstract: Carbohydrate-deficient transferrin proves to be the best marker of alcohol abuse. It allows objective detection so that therapeutic action can be started early, which is easier and more effective than in alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…[3,15] The major signs of SAH include markedly elevated jaundice and concomitant coagulopathy. [16] In agreement with the previous reports in patients with liver disease, [17][18][19][20] high levels of MCV, the AST/ALT ratio, TBIL, and INR were observed in SAH. Therefore, it would be important and necessary to do more studies on the prognosis of Chinese patients with SAH.…”
Section: Discussionsupporting
confidence: 81%
“…[3,15] The major signs of SAH include markedly elevated jaundice and concomitant coagulopathy. [16] In agreement with the previous reports in patients with liver disease, [17][18][19][20] high levels of MCV, the AST/ALT ratio, TBIL, and INR were observed in SAH. Therefore, it would be important and necessary to do more studies on the prognosis of Chinese patients with SAH.…”
Section: Discussionsupporting
confidence: 81%
“…Many heavy drinkers had a level of CDT<2.1%, but this is not necessarily a misclassification because this is usually found in 1 of 6 patients with excessive chronic ethanol consumption. 7 We found that a chronic ethanol consumption of ≥300 g per week is independently associated with a higher severity of the neurological deficit. There is not necessarily a causal relationship between ethanol consumption and stroke severity, but just a statistical association, that could be related to confounders that were not included in the analysis.…”
Section: Discussionmentioning
confidence: 71%
“…As the specificity of a CDT>2.5% for excessive chronic ethanol consumption is high, 7 there were probably <5% of heavy drinker misclassified. Many heavy drinkers had a level of CDT<2.1%, but this is not necessarily a misclassification because this is usually found in 1 of 6 patients with excessive chronic ethanol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that a combination of CDT and GGT, namely GGT-CDT, can have higher sensitivity than single markers alone in detecting excessive drinkers [16]. Although MCV is often included in the current standards of biomarkers for excessive drinking, sensitivity of MCV in detection of habitual drinkers is lower than those of GGT as demonstrated in several reports [17,18]. In the present study, the positive rates of %CDT and GGT in habitual heavy drinkers consuming more than 60 g of alcohol per day were 58.3% and 41.7%, respectively in all the heavy drinkers ( Figures 1 and 2); 58% and 44%, respectively, in males and 58% and 17%, respectively, in females.…”
Section: Discussionmentioning
confidence: 99%